A Guide to Co-Teaching for the SLP: A Tutorial. (February 2021) - Heisler, Lori A.; Thousand, Jacqueline S.
Co-teaching is when two or more people share instructional responsibility for all of the students assigned to them. There are many benefits to students when speech–language pathologists (SLPs) participate in co-teaching relationships with other educators and specialists by working on functional goals in the natural environment of the classroom. With co-teaching, SLPs are able to provide services to students who are eligible for special education and also support their school community through a model of multitiered system of support for all children. The purpose of this tutorial is to provide SLPs with a rationale for collaborative interventions and co-teaching, information about the four co-teaching approaches, planning and collaboration issues partners need to address, and tips for success.